2022
DOI: 10.1155/2022/1546297
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic-Induced Injury of Mouse Hepatocytes through Lysosome and Mitochondria: An In Vitro Study

Abstract: Background and Aims. The cellular mechanism of liver injury related to arsenic toxicity is ill defined. It is thought that oxidative stress and mitochondrial dysfunction may play some role in arsenic-induced liver damage. In this study, we evaluated subcellular events within the primary cultured mouse hepatocytes when exposed to inorganic arsenic. Methods. Primary cultured mouse hepatocytes were treated with 10 μM arsenic for different time periods. Reactive oxygen species (ROS) formation, functional changes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, As(III) (As 2 O 3 and AsO 2 − ) brought about oxidative stress. The stress manifested in MPTP opening, mitochondrial swelling, ∆Ψ mito decline, a decrease in ATP, reduced glutathione, an ROS production increase, and cytochrome c release in investigations with PC12 cells, Hela cells, isolated rat hepatocytes, rat cardiomyocyte H9c2 cells, L02 hepatocytes, lung bronchial epithelial HBE cells, Hela cells, mouse insulinoma MIN6 cells, laryngeal squamous carcinoma Hep-2 cells, Chang human hepatocytes, mouse embryonic fibroblasts, mouse hepatocytes, human hepatocellular carcinoma HepG2 cells, colon cancer HT-29 cells, cervical cancer cells, primary cultured mouse hepatocytes, and human myeloid leukemia U937 cells [161,162,271,279,[281][282][283][284][285][287][288][289][290][291][292][293][294][295][296]. In addition, AsO 2 − in L02 hepatocytes induced ERK signaling to activate both apoptosis and mitophagy [282] along with ferroptosis in mouse insulinoma MIN6 cells or PC-12 cells [283,297].…”
Section: Al(iii) Ga(iii) and In(iiimentioning
confidence: 99%
“…However, As(III) (As 2 O 3 and AsO 2 − ) brought about oxidative stress. The stress manifested in MPTP opening, mitochondrial swelling, ∆Ψ mito decline, a decrease in ATP, reduced glutathione, an ROS production increase, and cytochrome c release in investigations with PC12 cells, Hela cells, isolated rat hepatocytes, rat cardiomyocyte H9c2 cells, L02 hepatocytes, lung bronchial epithelial HBE cells, Hela cells, mouse insulinoma MIN6 cells, laryngeal squamous carcinoma Hep-2 cells, Chang human hepatocytes, mouse embryonic fibroblasts, mouse hepatocytes, human hepatocellular carcinoma HepG2 cells, colon cancer HT-29 cells, cervical cancer cells, primary cultured mouse hepatocytes, and human myeloid leukemia U937 cells [161,162,271,279,[281][282][283][284][285][287][288][289][290][291][292][293][294][295][296]. In addition, AsO 2 − in L02 hepatocytes induced ERK signaling to activate both apoptosis and mitophagy [282] along with ferroptosis in mouse insulinoma MIN6 cells or PC-12 cells [283,297].…”
Section: Al(iii) Ga(iii) and In(iiimentioning
confidence: 99%
“…However, As is also found to inhibit the autophagosome-lysosome fusion in NIH 3T3 cells by co-tranfected with the monomeric red fluorescent protein (mRFP)-GFP-LC3 fluorescent tandem reporter and LAMP1-CFP constructs (Dodson et al 2018 ). Furthermore, as to the impaired lysosome-dependent degradation process, As-induced low levels of ROS could cause LMP and subsequent release of CTSB to the hepatic cytoplasm (Santra et al 2022 ). Wang et al have observed that trivalent arsenic exposure impairs lysosomal membrane stability in earthworms (Wang et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%